Nursing Care for Patients with Disorders in Normal Breast Cell Growth (Mammary Fibroadenoma) in the Nursing Room - Hartaty, Hartaty; Kristina, Yunita; Hastutiningtyas, Wahidyanti Rahayu (International Journal of Health Sciences, 2024)
Fibroadenoma mammae is a benign tumor that often occurs in the breast that originates from fibrous tissue (mesenchyme) and glandular tissue (epithelium) in the breast. Fibroadenoma mammae is a disorder in the growth of normal breast cells where abnormal cells arise from normal cells, multiply and infiltrate lymphatic tissue and blood vessels. The cause of breast tumors has not been determined, but there are several genetic factors. Breast cancer shows malignant proliferation of epithelial cells that limit the ducts or lobes of the breast. Initially there is only cell hyperplasia with the development of atypical cells and then continues to carcinoma in situ and cells become masses. Steroid hormones produced by the ovaries also play a role in the formation of breast tumors. The purpose of the study was to gain real experience in implementing nursing care for patients with Breast Tumors in the Treatment Room of the Regional General Hospital. This study uses a descriptive research approach, the subject of the study is to use one patient according to the specified inclusion and exclusion data. Data were obtained by conducting direct observation and interview assessments with patients. The results of the assessment obtained data from patients suffering from fibroadenomae mammae. Analysis of nursing diagnosis data is the risk of pain comfort, sleep pattern disorders and activities. Nursing planning is checking blood pressure, giving injections, teaching breathing relaxation techniques in assessing pain scales, giving injections, cefotaxin I g / IV, giving Ketorolac 30mg / IV injections. The conclusion of this case study gets an overview of nursing care with fibroadenomae mammae.